Marketingový audit vybrané společnosti - Ermolin, Daniil (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Tato diplomová práce se zabývá provedením marketingového auditu společnosti Tungaloy Rus se zvláštním zaměřením na spokojenost jejích pracovníků. V teoretické části diplomové práce se vymezuje pojem a význam marketingového auditu, a taktéž podstata spokojenosti pracovníků a moderní přístupy k jejímu měření. V analytické části diplomové práce se provádí marketingový audit společnosti Tungaloy Rus a průzkum spokojenosti jejích pracovníků. V návrhové části diplomové práce se na základě zjištěných informací navrhují doporučení ke zlepšení současného stavu marketingové činnosti společnosti.

The master‘s thesis deals with marketing auditing of company Tungaloy Rus with a special focus on its employees’ satisfaction. The theoretical part of the thesis defines the meaning and importance of marketing audit, as well as the concept of employees’ satisfaction and modern approaches to its measurement. The analytical part of the thesis focuses on performing the marketing audit of company Tungaloy Rus and surveying the satisfaction of its employees. The proposal part of the thesis aims to making a set of recommendations based on the results of the marketing audit and the satisfaction research, which leads to improving the company's marketing activities.
Marketing Audit of a Company
Keywords: marketingový audit; marketingová činnost; spokojenost pracovníků; pracovní život; hodnocení zaměstnavatele; velkoobchodní společnost; obráběcí nástroje; marketing audit; marketing activities; employees’ satisfaction; working life; employer evaluation; wholesale company; cutting tools